RANCANG BANGUN ALAT UJI KEKAKUAN PEGAS - Rachmanda, Reza Irfani; Wulandari, Diah (Jurnal Rekayasa Mesin, 2021)
Actually, this spring is also discussed in physics, wherefrom the spring we can calculate the increase in the length of the spring based on the given load. Spring is an elastic object used to store mechanical energy. Springs are usually made of steel. There are several spring designs. In everyday usage, this term refers to Coil Spring. Springs are also found in motorcycle suspension systems. In motorcycles, springs have the function of absorbing shock from the road and wheel vibrations so that they are not transmitted directly to the vehicle body. In addition, springs are also useful for increasing tire grip on the road surface. In the teaching and learning process in physics courses, there are still obstacles, namely, there is no vibration practicum tool, from the desire to know the design of the tool, and to know the results of the tool's performance, the author can apply the results of the lectures that have been taken in the previous semester. This design aims to determine the design of the tool and the results of the performance of the spring stiffness test equipment. The design of the trainer uses the Research and Development (R&D) method or experimental-based development design. The spring stiffness test is a test of the change in the length of the spring when it is given a certain load. This study aims to design, manufacture and test spring stiffness test equipment. In the design process, it is necessary to calculate the frame, function, and type of material to be used. The analysis carried out includes determining the electric motor, determining the material used, knowing the design of the tool, and knowing the results of the performance of the tool later. After analyzing the work of the tool and analyzing the test results, a conclusion will be obtained that can be drawn based on the existing data.